Building materials - Duggal, S.K. ([S.l.] : New Age International Pvt. Ltd., 2010)
This revised edition contains the manufacturing processes physical and mechanical properties, economics and applications of building materials in sequential and lucid manner. Updated coverage of the newly developed building materials, combined with a plethora of exercises and objective type questions, makes this an excellent offering on the subject. Besides serving as a textbook for students of undergraduate programmes in the discipline of civil engineering, the revised edition will also be useful for the students undertaking course on concrete technology.